Revision of Bairdiella (Sciaenidae: Perciformes) from the western South Atlantic, with insights into its diversity and biogeography - Marceniuk, Alexandre Pires [UNESP]; Garcia Molina, Eduardo; Caires, Rodrigo Antunes; Rotundo, Matheus Marcos; Wosiacki, Wolmar Benjamin; Oliveira, Claudio [UNESP] (Soc Brasileira Ictiologia, 2019)
The sciaenid genus Bairdiella comprises a group of relatively small fishes found in inshore waters and estuaries of the western Atlantic and eastern Pacific. Despite recent analyses of the phylogenetic relationships of Bairdiella, there has been no comprehensive revision of the alpha taxonomy of the species of the genus. Bairdiella ronchus from the western Atlantic, has a complex taxonomic history, with four junior synonyms recognized. Based on morphological and molecular evidence, this study indicates that B. ronchus represents a species complex. The species is therefore redescribed and its geographic range is redefined. Bairdiella veraecrucis, which is currently recognized as a junior synonym of B. ronchus, is revalidated, and a new species of the genus is described from the Atlantic coast of Brazil. Finally, inferences are made on the diversity and biogeography of the B. ronchus species complex.
Keywords: Biogeographic patterns; New species; Species complex; Taxonomy; Western Atlantic